EUV spectra from highly charged terbium ions in optically thin and thick plasmas. (29th January 2015) - Suzuki, C; Koike, F; Murakami, I; Tamura, N; Sudo, S; Long, E; Sheil, J; White, E; O'Reilly, F; Sokell, E; Dunne, P; O'Sullivan, G
Abstract: We have observed extreme ultraviolet (EUV) spectra from terbium (Tb) ions in optically thin and thick plasmas for a comparative study. The experimental spectra are recorded in optically thin, magnetically confined torus plasmas and dense laser-produced plasmas (LPPs). The main feature of the spectra is quasicontinuum emission with a peak around 6.5-6.6 nm, the bandwidth of which is narrower in the torus plasmas than in the LPPs. A comparison between the two types of spectra also suggests strong opacity effects in the LPPs. A comparison with the calculated line strength distributions gives a qualitative interpretation of the observed spectra.